Polyelectrolyte-surfactant complexes (PESCs) composed of oppositely charged components. (May 2018) - Gradzielski, Michael; Hoffmann, Ingo
Abstract: Recent developments in the field of oppositely charged polyelectrolyte-surfactant complexes (PESCs) have been reviewed. Among the many developments in that field in particular very interesting is certainly the discovery of still new types of structural arrangements that arise from the complexity of the prevailing interactions, both in terms of electrostatics, as well as steric and specific interactions. More complex structures often arise from the architecture of the polyelectrolyte, such as the use of block copolymers or hydrophobically modified polyelectrolytes. However, also the surfactant plays a role in the PESC structure and for instance bilayer forming surfactants can be induced by polyelectrolyte to form multilamellar assemblies. Of course, PESCs may exhibit responsiveness to changes of pH, temperature, chemical environment etc. and this even in a complex fashion as the polyelectrolyte and surfactant may respond here in a different fashion. Interesting observations also concern the control of rheological properties by PESCs that depend strongly on the properties of the polyelectrolyte and the extension of the formed mixed aggregates, as well as their bridging. An old topic is coacervate formation in such systems, but one that currently receives renewed attention, as various aspects here are still not fully understood and at the same time they are very promising for further applications in separation/sequestration. Often overlooked is the fact that PESCs are typically not static entities but instead highly dynamic systems and recent neutron spin-echo (NSE) measurements indicate that the local dynamics of polyelectrolyte chains is only little affected by the incorporation within such aggregates. Therefore PESCs are still a highly fascinating class of self-assembled structures, where a large number of interesting developments may still be expected in the future. Graphical abstract: Unlabelled Image Highlights: Polyelectrolyte-surfactant complexes (PESCs) can have largely different structures. PESCs are versatile systems for rheological control. Coacervate formation by PESCs is interesting for liquid-liquid extraction. Polyelectrolyte chains in PESCs are highly mobile.